Mechanism of Pulsatile GnRH Release in Primates: Unresolved Questions - Terasawa, Ei (Mol Cell Endocrinol, 2019)
The pulsatility of GnRH release is essential for reproductive function. The key events in reproductive function, such as puberty onset and ovulatory cycles, are regulated by the frequency and amplitude modulation of pulsatile GnRH release. Abnormal patterns of GnRH pulsatility are seen in association with disease states, such as polycystic ovarian syndrome and anorexia nervosa. Recent studies with physiological, track-tracing, optogenetic and electrophysiological recording experiments indicate that a group of kisspeptin neurons in the arcuate nucleus (ARC) of the hypothalamus are responsible for pulsatile GnRH release. Thus, the kisspeptin neuron in the ARC has been called the “GnRH pulse-generator.” However, a few pieces of evidence do not quite fit into this concept. This article reviews some old works and discusses unresolved issues on the mechanism of GnRH pulse generation.